Cerium-containing neodymium-iron-boron magnet steel and preparation method thereof

CN122800430APending Publication Date: 2026-09-22ANHUI ONE MAGNET ELECTRONIC CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611079055.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-20
Publication Date
2026-09-22

AI Technical Summary

Technical Problem

该方式虽然工艺简单,但存在如下不足:第一,Ce、Nd、Pr在合金中随机分布,Ce容易进入晶界区域或造成晶界稀土相组成不稳定,使晶界相润湿性下降,难以形成连续有效的磁隔离层

Benefits of technology

[0021]与现有技术相比,本发明提供了一种含铈钕铁硼磁钢及其制备方法,具备以下有益效果:通过含铈主相合金A和晶界调控合金B的双合金设计,将Ce主要引入R2Fe14B主相,同时通过富Nd/Pr晶界调控合金B在烧结和时效过程中的液相润湿和晶界重构作用,使Nd/Pr富集并保留于晶界区域,从而形成含Ce主相与富Nd/Pr连续晶界相共存的微观结构。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122800430A_ABST
    Figure CN122800430A_ABST
Patent Text Reader

Abstract

The application discloses a cerium-containing neodymium-iron-boron magnetic steel and a preparation method thereof, and belongs to the technical field of rare earth permanent magnet materials. 14 In the cerium-containing main phase alloy A, Ce enters R2Fe 14 B main phase as one of rare earth element components, and the content of Nd and / or Pr in the grain boundary regulating alloy B is higher than that of Ce; in step two, the cerium-containing main phase alloy A and the grain boundary regulating alloy B are respectively subjected to vacuum smelting and rapid solidification casting piece treatment to obtain a cerium-containing main phase rapid solidification casting piece and a grain boundary regulating rapid solidification casting piece; through the double-alloy design of the cerium-containing main phase alloy A and the grain boundary regulating alloy B, Ce is mainly introduced into the R2Fe 14 B main phase, and meanwhile, through the liquid phase wetting and grain boundary reconstruction of the Nd / Pr-rich grain boundary regulating alloy B in the sintering and aging process, Nd / Pr is enriched and retained in the grain boundary region, so that a microstructure in which the Ce-containing main phase and the Nd / Pr-rich continuous grain boundary phase coexist is formed.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of rare earth permanent magnet materials technology, specifically relating to a cerium-containing neodymium iron boron magnet and its preparation method. Background Technology

[0002] Sintered NdFeB permanent magnets, due to their high remanence, high coercivity, and high energy product, are widely used in new energy vehicle drive motors, wind power generation, energy-saving compressors, robots, consumer electronics, and industrial servo motors. Traditional high-performance NdFeB magnets primarily rely on rare earth elements such as Nd, Pr, Dy, and Tb, with Nd and Pr being the constituents of R2Fe. 14 Key elements of the boron main phase, Dy and Tb, are often used to improve the coercivity of magnets. However, the prices of Nd, Pr, Dy, and Tb resources fluctuate significantly, especially the high cost of heavy rare earth elements, resulting in high manufacturing costs for high-performance magnets.

[0003] Ce is a relatively abundant and low-cost element among rare earth resources. Replacing Nd / Pr with Ce in the production of NdFeB magnets can reduce the cost of raw materials and improve the overall utilization rate of rare earth resources. However, Ce₂Fe 14 The anisotropic field and magnetocrystalline anisotropy of the B phase are typically lower than those of Nd₂Fe. 14 B and Pr2Fe 14 B. Excessive Ce entering the main phase or grain boundary phase can easily lead to a decrease in the intrinsic coercivity Hcj and the maximum energy product (BH)max of the magnet. Therefore, how to maintain high coercivity and high energy product under high Ce content is a key issue in the industrial application of cerium-containing NdFeB magnets.

[0004] Existing cerium-containing NdFeB magnets are typically produced using a single-alloy method, which involves the one-time batching, melting, powdering, and sintering of Ce, Nd, Pr, Fe, B, and small amounts of additives. While this method is simple, it has the following drawbacks: First, Ce, Nd, and Pr are randomly distributed in the alloy, and Ce easily enters grain boundary regions or causes instability in the rare earth phase composition at grain boundaries, reducing the wettability of the grain boundary phase and making it difficult to form a continuous and effective magnetic isolation layer. Second, the insufficient Nd / Pr enrichment at grain boundaries between Ce-containing main phase grains leads to enhanced inter-grain exchange coupling, making it easier for antimagnetic domains to extend across grains, thus reducing coercivity. Summary of the Invention

[0005] The purpose of this invention is to provide a cerium-containing NdFeB magnet and its preparation method. This method utilizes a dual-alloy design of a cerium-containing main phase alloy A and a grain boundary control alloy B, enabling Ce to primarily participate in the formation of Ce-containing R₂Fe. 14The B main phase enables the grain boundary control alloy B to form a continuous Nd / Pr rich grain boundary phase during sintering and aging. At the same time, by controlling the average particle size D2 of the grain boundary control alloy powder to be smaller than the average particle size D1 of the cerium-containing main phase alloy powder, the grain boundary control alloy powder can more easily fill the gaps between the main phase powder particles, thereby forming a continuous Nd / Pr rich grain boundary phase that encapsulates the Ce-containing main phase grains during sintering and aging, improving the grain boundary magnetic isolation effect and coercivity.

[0006] To achieve the above objectives, the present invention provides the following technical solution: a method for preparing cerium-containing neodymium iron boron magnets, comprising the following steps: Step 1: Prepare cerium-containing main phase alloy A and grain boundary control alloy B respectively; in cerium-containing main phase alloy A, Ce enters R2Fe as one of the rare earth elements. 14 The B main phase, wherein the content of Nd and / or Pr in the grain boundary controlled alloy B is higher than the content of Ce.

[0007] Step 2: Vacuum melting and rapid solidification casting of cerium-containing main phase alloy A and grain boundary control alloy B are performed respectively to obtain cerium-containing main phase rapid solidification sheet and grain boundary control rapid solidification sheet.

[0008] Step 3: The cerium-containing main phase rapid solidification sheet and the grain boundary control rapid solidification sheet are respectively subjected to hydrogen crushing and air jet milling to obtain cerium-containing main phase alloy powder with an average particle size of D1 and grain boundary control alloy powder with an average particle size of D2, where D2 < D1.

[0009] Step 4: Under an inert atmosphere, mix the cerium-containing main phase alloy powder and the grain boundary control alloy powder, and add antioxidants and lubricants to obtain mixed magnetic powder.

[0010] Step 5: The mixed magnetic powder is oriented and shaped in an orientation magnetic field, and then subjected to cold isostatic pressing to obtain an orientation compact.

[0011] Step Six: The orientation compact is subjected to vacuum sintering and multi-stage aging treatment to form a continuous grain boundary phase rich in Nd / Pr during the sintering and aging process of the grain boundary control alloy B, and the continuous grain boundary phase rich in Nd / Pr encapsulates Ce-containing R2Fe. 14 By controlling the B main phase grains, Ce is suppressed from entering the grain boundary phase and Nd / Pr is retained in the grain boundary region, resulting in cerium-containing NdFeB magnets.

[0012] Further, the cerium-containing main phase alloy A comprises, by mass percentage: Nd 12.0-24.0%, Pr 3.0-8.0%, Ce 3.0-10.0%, B 0.90-1.08%, Co 0.2-2.0%, Al 0.10-0.80%, Cu 0.05-0.50%, Ga 0.03-0.40%, Zr 0.02-0.20%, with the balance being Fe and unavoidable impurities; wherein Ce accounts for 15-45% of the total molar amount of rare earth elements in the cerium-containing main phase alloy A.

[0013] Further, the grain boundary control alloy B comprises, by mass percentage: Nd 35.0-65.0%, Pr 10.0-30.0%, Ce 0-5.0%, Cu 5.0-20.0%, Ga 2.0-12.0%, Al 1.0-8.0%, Co 0-8.0%, with the balance being Fe and unavoidable impurities; the total mass percentage of Nd and Pr in the grain boundary control alloy B is not less than 50.0%, and the mass percentage of Ce is not more than 5.0%.

[0014] Furthermore, in step two, the vacuum degree of vacuum melting is not higher than 5 Pa, and the melting temperature is 1350-1500℃; the rapid solidification casting is cooled by water-cooled copper rollers with a linear speed of 1.0-3.5 m / s, the thickness of the obtained cerium-containing main phase rapid solidification sheet is 0.15-0.45 mm, and the thickness of the obtained grain boundary controlled rapid solidification sheet is 0.10-0.35 mm.

[0015] Furthermore, in step three, hydrogen crushing includes hydrogen absorption and dehydrogenation treatments; the hydrogen absorption pressure is 0.08-0.20 MPa, the hydrogen absorption temperature is 20-120℃, the dehydrogenation temperature is 450-600℃, and the dehydrogenation time is 2-6 h; the air jet milling is carried out under nitrogen or argon protection, the D1 of the cerium-containing main phase alloy powder is 2.6-4.2 μm, the D2 of the grain boundary regulating alloy powder is 0.8-2.5 μm, and the D2 / D1 ratio is 0.25-0.80.

[0016] Further, in step four, the mass ratio of cerium-containing main phase alloy powder to grain boundary control alloy powder is 88-97:3-12; the amount of antioxidant added is 0.02-0.20% of the total mass of cerium-containing main phase alloy powder and grain boundary control alloy powder, and the amount of lubricant added is 0.02-0.15% of the total mass of cerium-containing main phase alloy powder and grain boundary control alloy powder; the oxygen content during the mixing process is controlled below 1000 ppm.

[0017] Furthermore, in step five, the orientation magnetic field strength is 1.5-2.5T, the orientation forming pressure is 60-120MPa, the cold isostatic pressing pressure is 150-250MPa, the holding time is 30-180s, and the orientation direction of the obtained orientation compact is the easy magnetization direction of the cerium-containing neodymium iron boron magnet.

[0018] Furthermore, in step six, the vacuum degree of vacuum sintering is no higher than 5 × 10⁻⁶. - ²Pa, sintering temperature is 1030-1085℃, holding time is 2-6h; multi-stage aging treatment includes first-stage aging and second-stage aging, first-stage aging temperature is 850-930℃, holding time is 1-4h, second-stage aging temperature is 450-560℃, holding time is 2-6h.

[0019] Furthermore, after multi-stage aging treatment, Ce-containing R2Fe is formed in the cerium-containing NdFeB magnets. 14 The main phase consists of a B phase, an Nd / Pr-rich grain boundary phase, and a low-melting-point grain boundary modified phase containing Cu, Ga, and Al. The Nd / Pr-rich grain boundary phase is continuously distributed along the grain boundaries of the main phase, and the length coverage of the Nd / Pr-rich grain boundary phase along the grain boundaries of the main phase is not less than 80%. The low-melting-point grain boundary modified phase containing Cu, Ga, and Al is located in the grain boundary triangle region and / or at the grain boundary.

[0020] This invention also provides a cerium-containing NdFeB magnet, prepared by the above-described method; the cerium-containing NdFeB magnet comprises, by mass percentage: 28.5-32.5% total rare earth elements, 0.88-1.08% B, 0.2-2.0% Co, 0.10-0.90% Al, 0.05-0.80% Cu, 0.05-0.60% Ga, 0.02-0.20% Zr, with the balance being Fe and unavoidable impurities; wherein Ce accounts for 15-45% of the total molar amount of rare earth elements, and the cerium-containing NdFeB magnet has a Ce-containing R2Fe. 14 The main phase consists of a B-type phase and a Nd / Pr-rich continuous grain boundary phase, wherein the Nd / Pr-rich continuous grain boundary phase encapsulates Ce-containing R2Fe. 14 The cerium-containing neodymium iron boron magnet has B main phase grains, and its intrinsic coercivity Hcj is not less than 15 kOe, and its maximum energy product (BH)max is not less than 35 MGOe.

[0021] Compared with the prior art, the present invention provides a cerium-containing NdFeB magnet and its preparation method, which has the following beneficial effects: through the dual alloy design of cerium-containing main phase alloy A and grain boundary control alloy B, Ce is mainly introduced into R2Fe. 14The B main phase, along with the liquid phase wetting and grain boundary reconstruction of alloy B during sintering and aging processes through Nd / Pr-rich grain boundaries, allows Nd / Pr to be enriched and retained in the grain boundary region, thus forming a microstructure in which the Ce-containing main phase and the Nd / Pr-rich continuous grain boundary phase coexist.

[0022] This invention controls the average particle size D2 of the grain boundary control alloy powder to be smaller than the average particle size D1 of the cerium-containing main phase alloy powder, making it easier for the finer grain boundary control alloy powder to fill between the cerium-containing main phase powder particles. In the early stage of sintering, a low-melting-point Nd / Pr-rich liquid phase is preferentially formed along the grain boundary, thereby improving grain boundary wettability and grain boundary coverage.

[0023] This invention achieves its goal by encapsulating Ce-containing R2Fe with a continuous Nd / Pr-rich grain boundary phase. 14 B-phase grains reduce direct contact and exchange coupling between Ce-containing phase grains, suppressing the expansion of antimagnetic domains across grains, thus achieving high intrinsic coercivity and maximum energy product even with high Ce content.

[0024] This invention introduces low-melting-point grain boundary modifiers such as Cu, Ga, and Al into grain boundary control alloy B, which enhances the fluidity, wettability, and stability of the grain boundary phase during sintering and aging, thus facilitating the formation of a continuous Nd / Pr-rich grain boundary phase while reducing grain boundary defects and Fe-rich phase residues.

[0025] This invention achieves full densification of the main phase grains by controlling the sintering temperature and multi-stage aging process, while simultaneously enabling the grain boundary phases to redistribute and adjust their composition during the first and second stages of aging, thereby improving the overall magnetic properties and batch stability of the magnets. Attached Figure Description

[0026] Figure 1 The images show the SEM morphology and particle size distribution of the cerium-containing main phase alloy powder and the grain boundary controlled alloy powder in Example 2 of the present invention, and the particle size distribution of the powder without particle size gradient in Comparative Example 2. Figure 2 The SEM-BSE images and EDS surface scan comparison images of Ce, Nd, and Pr elements are shown for the cerium-containing NdFeB magnet prepared by the dual alloy method in Example 2 of this invention and the magnet prepared by the single alloy method in Comparative Example 1. Figure 3 Line scan comparison of Ce, Nd, and Pr elements at grain boundaries between the magnet prepared by the low Ce grain boundary controlled alloy in Example 2 of the present invention and the magnet prepared by the high Ce grain boundary controlled alloy in Comparative Example 3. Figure 4 The images show a comparison of SEM images of the Nd / Pr-rich grain boundary phase length coverage of the magnets prepared in Embodiment 2, Comparative Example 1, Comparative Example 2, and Comparative Example 5 of this invention. Detailed Implementation

[0027] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.

[0028] Please see Figures 1-4 This invention provides a technical solution for cerium-containing neodymium iron boron magnets and their preparation method: In the following examples and comparative examples, the powder particle size D50 was determined according to GB / T 19077-2024 "Particle Size Analysis by Laser Diffraction"; the magnetic properties were determined according to GB / T 3217-2013 "Magnetic Test Methods for Permanent Magnet (Hard Magnetic) Materials"; the grade and magnetic property evaluation of sintered NdFeB materials were based on GB / T 13560-2017 "Sintered NdFeB Permanent Magnet Materials"; the length measurement in the statistics of micron-level length and grain boundary coverage was based on GB / T 16594-2008 "General Rules for Scanning Electron Microscopy Measurement Methods of Micron-Level Lengths"; and the EDS elemental quantitative analysis was based on GB / T 17359-2023 "Quantitative Analysis of Elements with Atomic Number Not Less Than 11 by Energy Dispersive X-ray Spectroscopy". Numerical rounding was performed according to GB / T 8170-2008.

[0029] The length coverage of Nd / Pr-rich grain boundary phases in the examples and comparative examples was statistically determined as follows: Sintered magnets were cut perpendicularly to the orientation direction, and then sequentially inlaid, ground, polished, and ion-beam cleaned. Twenty fields of view were randomly selected in SEM backscatter mode, and EDS surface scanning was used to identify regions at the main phase grain boundaries where the Nd and / or Pr content was higher than the average Nd and / or Pr content of adjacent main phase grains. These regions were identified as Nd / Pr-rich grain boundary phases. The length coverage of Nd / Pr-rich grain boundary phases was calculated using the following formula: Nd / Pr rich grain boundary phase length coverage (%) = (Length of main phase grain boundary covered by Nd / Pr rich grain boundary phase / Total length of main phase grain boundary phase) × 100%.

[0030] In this invention, "R2Fe containing Ce is encapsulated" 14 "B-phase grains" refer to Ce-containing main phase grains whose outer periphery, in SEM backscattered image and EDS elemental surface scan, is continuously or nearly continuously covered by grain boundary phases rich in Nd and / or Pr. This isolates adjacent Ce-containing main phase grains from each other by Nd / Pr-rich grain boundary phases, forming a core-shell grain boundary network structure. This structure differs from the structure in ordinary single alloying where Ce, Nd, and Pr are randomly distributed in the main phase and grain boundaries, and also differs from the structure in grain boundary-controlled alloys where local segregation does not form a continuous grain boundary coating.

[0031] Example 1 A cerium-containing main phase alloy A was prepared, with the following composition by mass percentage: Nd 20.5%, Pr 4.5%, Ce 4.5%, B 0.90%, Co 0.2%, Al 0.10%, Cu 0.05%, Ga 0.03%, Zr 0.02%, with the balance being Fe and unavoidable impurities. Ce accounts for approximately 15.2% of the total molar amount of rare earth elements in the cerium-containing main phase alloy A.

[0032] Grain boundary control alloy B was prepared with the following composition by mass percentage: Nd 35.0%, Pr 15.0%, Ce 0%, Cu 5.0%, Ga 2.0%, Al 1.0%, Co 0%, with the balance being Fe and unavoidable impurities.

[0033] Cerium-containing main phase alloy A and grain boundary control alloy B were respectively placed in a vacuum induction melting furnace, evacuated to 4.5 Pa, and melted at 1350℃. They were then poured into water-cooled copper rollers for rapid solidification casting. The linear speed of the copper rollers was 1.0 m / s, resulting in a cerium-containing main phase rapid solidification sheet with a thickness of 0.45 mm and a grain boundary control rapid solidification sheet with a thickness of 0.35 mm.

[0034] Two types of rapidly solidifying flakes were subjected to hydrogen degradation treatment at a hydrogen absorption pressure of 0.08 MPa, a hydrogen absorption temperature of 20 °C, a dehydrogenation temperature of 450 °C, and a dehydrogenation time of 2 h. After dehydrogenation, the flakes were pulverized by air jet milling under nitrogen protection to obtain a cerium-containing main phase alloy powder with a D1 of 2.6 μm and a grain boundary regulation alloy powder with a D2 of 0.8 μm, with a D2 / D1 ratio of 0.31.

[0035] Under nitrogen protection, cerium-containing main phase alloy powder and grain boundary control alloy powder were mixed at a mass ratio of 97:3. Antioxidant and lubricant of 0.02% of the total powder mass were added. The oxygen content was controlled at 720ppm during the mixing process to obtain mixed magnetic powder.

[0036] The mixed magnetic powder was oriented and shaped in a 1.5T orientation magnetic field at a pressure of 60MPa, followed by cold isostatic pressing at 150MPa for 30s to obtain an oriented compact. The oriented compact was then placed in a vacuum sintering furnace at a vacuum degree of 4.5×10⁻⁶. - Sintering was carried out at 1030℃ for 2 hours under ²Pa conditions; then primary aging and secondary aging were performed, with the primary aging temperature at 850℃ and holding time at 1 hour, and the secondary aging temperature at 450℃ and holding time at 2 hours, to obtain cerium-containing neodymium iron boron magnets.

[0037] Example 2 A cerium-containing main phase alloy A was prepared, with the following composition by mass percentage: Nd 18.0%, Pr 5.5%, Ce 6.5%, B 1.00%, Co 1.0%, Al 0.40%, Cu 0.25%, Ga 0.20%, Zr 0.10%, with the balance being Fe and unavoidable impurities. Ce accounts for approximately 21.9% of the total molar amount of rare earth elements in the cerium-containing main phase alloy A.

[0038] Grain boundary control alloy B was prepared with the following composition by mass percentage: Nd 50.0%, Pr 20.0%, Ce 2.0%, Cu 12.0%, Ga 6.0%, Al 4.0%, Co 4.0%, with the balance being Fe and unavoidable impurities.

[0039] Cerium-containing main phase alloy A and grain boundary control alloy B were respectively placed in a vacuum induction melting furnace, evacuated to 3 Pa, and melted at 1420℃. They were then poured into a water-cooled copper roller for rapid solidification casting. The linear speed of the copper roller was 2.2 m / s, resulting in a cerium-containing main phase rapid solidification sheet with a thickness of 0.30 mm and a grain boundary control rapid solidification sheet with a thickness of 0.22 mm.

[0040] Two types of rapidly solidifying flakes were subjected to hydrogen degradation treatment at a hydrogen absorption pressure of 0.14 MPa, a hydrogen absorption temperature of 80 °C, a dehydrogenation temperature of 520 °C, and a dehydrogenation time of 4 h. After dehydrogenation, the flakes were pulverized by air jet milling under nitrogen protection to obtain a cerium-containing main phase alloy powder with a D1 of 3.4 μm and a grain boundary regulation alloy powder with a D2 of 1.6 μm, with a D2 / D1 ratio of 0.47.

[0041] Under nitrogen protection, cerium-containing main phase alloy powder and grain boundary control alloy powder were mixed at a mass ratio of 93:7. 0.10% of the total powder mass of antioxidant and 0.08% of lubricant were added. During the mixing process, the oxygen content was controlled at 650 ppm to obtain mixed magnetic powder.

[0042] The mixed magnetic powder was oriented and shaped in a 2.0T orientation magnetic field at a pressure of 90MPa, followed by cold isostatic pressing at 200MPa for 90s to obtain an oriented compact. The oriented compact was then placed in a vacuum sintering furnace at a vacuum degree of 3.0×10⁻⁶. - Sintering was carried out at 1060℃ for 4 hours under ²Pa conditions; then primary aging and secondary aging were performed, with the primary aging temperature at 890℃ and a holding time of 2 hours, and the secondary aging temperature at 510℃ and a holding time of 4 hours, to obtain cerium-containing neodymium iron boron magnets.

[0043] SEM backscattering and EDS surface scanning of the magnets prepared in Example 2 revealed that the low-brightness Ce-containing main phase grains were completely or nearly completely encapsulated and isolated by the high-brightness Nd / Pr-rich grain boundary phases, forming a core-shell grain boundary network structure. This Nd / Pr-rich grain boundary phase is continuously distributed along the boundaries of the main phase grains, which reduces direct contact between adjacent Ce-containing main phase grains and suppresses exchange coupling and demagnetization domain expansion. This is a key reason why Example 2 still achieved high Hcj and good squareness of the demagnetization curve under Ce-containing conditions.

[0044] Example 3 A cerium-containing main phase alloy A was prepared, with the following mass percentages: Nd 12.0%, Pr 3.0%, Ce 10.0%, B 1.08%, Co 2.0%, Al 0.80%, Cu 0.50%, Ga 0.40%, Zr 0.20%, with the balance being Fe and unavoidable impurities. Ce accounts for approximately 40% of the total molar amount of rare earth elements in the cerium-containing main phase alloy A.

[0045] Grain boundary control alloy B was prepared with the following composition by mass percentage: Nd 45.0%, Pr 15.0%, Ce 5.0%, Cu 20.0%, Ga 12.0%, Al 8.0%, Co 8.0%, with the balance being Fe and unavoidable impurities.

[0046] Cerium-containing main phase alloy A and grain boundary control alloy B were respectively placed in a vacuum induction melting furnace, evacuated to 2 Pa, and melted at 1500℃. They were then poured into a water-cooled copper roller for rapid solidification casting. The linear speed of the copper roller was 3.5 m / s, resulting in a cerium-containing main phase rapid solidification sheet with a thickness of 0.15 mm and a grain boundary control rapid solidification sheet with a thickness of 0.10 mm.

[0047] Two types of rapidly solidifying flakes were subjected to hydrogen degradation treatment at a hydrogen absorption pressure of 0.20 MPa, a hydrogen absorption temperature of 120 °C, a dehydrogenation temperature of 600 °C, and a dehydrogenation time of 6 h. After dehydrogenation, the flakes were pulverized by air jet milling under argon protection to obtain a cerium-containing main phase alloy powder with a D1 of 4.2 μm and a grain boundary control alloy powder with a D2 of 2.5 μm, with a D2 / D1 ratio of 0.60.

[0048] Under argon protection, cerium-containing main phase alloy powder and grain boundary control alloy powder were mixed at a mass ratio of 88:12. 0.20% of the total powder mass of antioxidant and 0.15% of lubricant were added. During the mixing process, the oxygen content was controlled at 820 ppm to obtain mixed magnetic powder.

[0049] The mixed magnetic powder was oriented and shaped in a 2.5T orientation magnetic field at a pressure of 120MPa, followed by cold isostatic pressing at 250MPa for 180s to obtain an oriented compact. The oriented compact was then placed in a vacuum sintering furnace at a vacuum degree of 2.0×10⁻⁶. -Sintering was carried out at 1085℃ for 6 hours under ²Pa conditions; then primary aging and secondary aging were performed, with the primary aging temperature at 930℃ and a holding time of 4 hours, and the secondary aging temperature at 560℃ and a holding time of 6 hours, to obtain cerium-containing neodymium iron boron magnets.

[0050] Example 4 Prepare a cerium-containing main phase alloy A, which by mass percentage is: Nd 14.0%, Pr 4.0%, Ce 9.0%, B 1.00%, Co 1.2%, Al 0.45%, Cu 0.30%, Ga 0.25%, Zr 0.10%, with the balance being Fe and unavoidable impurities.

[0051] Grain boundary control alloy B was prepared with the following composition by mass percentage: Nd 55.0%, Pr 20.0%, Ce 1.0%, Cu 10.0%, Ga 7.0%, Al 3.0%, Co 2.0%, with the balance being Fe and unavoidable impurities.

[0052] Cerium-containing main phase alloy A and grain boundary control alloy B were subjected to vacuum melting and rapid solidification casting, respectively. The melting temperature was 1450℃, the vacuum degree was 3Pa, and the copper roller linear speed was 2.5m / s. The resulting rapid solidification sheets were then subjected to hydrogen crushing and air jet milling to obtain cerium-containing main phase alloy powder with a D1 of 3.6μm and grain boundary control alloy powder with a D2 of 1.4μm, with a D2 / D1 ratio of 0.39.

[0053] Cerium-containing main phase alloy powder and grain boundary control alloy powder were mixed at a mass ratio of 90:10. 0.12% antioxidant and 0.10% lubricant were added to the total powder mass, and the mixture was prepared under nitrogen protection with an oxygen content not exceeding 700 ppm. The mixture was then oriented and formed in a 2.1T orientation magnetic field at a forming pressure of 95 MPa, followed by cold isostatic pressing at 220 MPa for 120 seconds. The compact was then vacuum sintered at 1065℃ for 4 hours, followed by primary aging at 900℃ for 2 hours and secondary aging at 520℃ for 4 hours to obtain cerium-containing NdFeB magnets.

[0054] Comparative Example 1 did not employ the dual alloying process of cerium-containing main phase alloy A and grain boundary control alloy B. Instead, the total composition of the two alloys in Example 2 was converted into a single alloy, followed by a single batching, melting, powdering, orientation forming, sintering, and aging process. Other sintering temperatures, aging temperatures, pressing conditions, and testing conditions were the same as in Example 2.

[0055] In Comparative Example 2, the grain boundary control alloy powder did not use a small particle size. The cerium-containing main phase alloy powder D1 was 3.4 μm, and the grain boundary control alloy powder D2 was 3.3 μm, with a D2 / D1 ratio of 0.97, meaning there was essentially no particle size gradient. Other alloy compositions, powder mixing ratios, sintering, and aging conditions were the same as in Example 2.

[0056] In Comparative Example 3, the Ce content in grain boundary control alloy B was increased to 12.0%, and the Nd and Pr contents were correspondingly reduced, so that the total mass percentage of Nd and Pr in grain boundary control alloy B was less than 50.0%. Other powder particle size, mixing ratio, sintering and aging conditions were the same as in Example 2.

[0057] In Comparative Example 4, the amount of grain boundary control alloy B added was 1.5%, that is, the mass ratio of cerium-containing main phase alloy powder to grain boundary control alloy powder was 98.5:1.5, which is lower than the range defined in this invention. Other alloy compositions, powder particle size, sintering and aging conditions were the same as in Example 2.

[0058] Comparative Example 5 was performed without secondary aging, only vacuum sintering at 1060℃ for 4 hours and primary aging at 890℃ for 2 hours. Other alloy compositions, powder particle sizes, mixing ratios, and molding conditions were the same as in Example 2.

[0059] Comparative Example 6 shows that the grain boundary controlled alloy powder has an excessively fine particle size, with D2 of 0.45 μm and a D2 / D1 ratio of 0.13, which is below the range defined in this invention. Other alloy compositions, powder mixing ratios, sintering, and aging conditions are the same as in Example 2.

[0060] Performance testing 1. Powder particle size test Cerium-containing main phase alloy powder and grain boundary control alloy powder were sampled separately, dispersed, and then the particle size distribution was measured using a laser particle size analyzer. The values ​​D10, D50, and D90 were recorded, with D50 serving as the characterization value for the average particle size D1 and D2.

[0061] 2. Magnetic property testing Sintered magnets were processed into standard test samples, and hysteresis loops and demagnetization curves were tested according to GB / T 3217-2013 to obtain remanence Br, intrinsic coercivity Hcj, coercivity Hcb, and maximum energy product (BH)max. Five parallel samples were tested for each group of samples, and the average value was taken.

[0062] 3. Density test The density of sintered magnets was determined using the Archimedes displacement method, and the relative density was calculated.

[0063] 4. Microstructure testing The magnetic steel sample was cut perpendicular to the orientation direction, then inlaid, ground, polished and ion-beam cleaned. The grain and grain boundary morphology was observed using SEM backscatter mode, and the distribution of Ce, Nd and Pr in the main phase and grain boundary phase was analyzed using EDS surface scanning and line scanning.

[0064] 5. Nd / Pr-rich grain boundary phase length coverage test Twenty SEM fields of view were randomly selected, and Nd / Pr-rich grain boundary phases were identified by EDS surface scanning. The length coverage was calculated as the ratio of the length of the main phase grain boundary covered by the Nd / Pr-rich grain boundary phase to the total length of the main phase grain boundary.

[0065] 6. Grain boundary phase Ce relative enrichment index test In each sample, select no fewer than 30 grain boundary regions and 30 main phase grain center regions, and determine the Ce content respectively, then calculate the relative enrichment index of Ce in the grain boundary phase: Ce relative enrichment index of grain boundary phase = average Ce content in grain boundary region / average Ce content in main phase grain center.

[0066] The lower the index, the less likely Ce is to enter the grain boundary region, and the more likely Nd / Pr is to be retained in the grain boundary region.

[0067] Test Results Table 1 shows the process parameters and microstructure test results for the examples and comparative examples.

[0068] Table 2 shows the magnetic performance test results of the examples and comparative examples.

[0069] Table 3 shows the grain boundary element distribution test results of Example 2 and Comparative Examples 1, 2, and 3.

[0070] As shown in Tables 1 to 3, Examples 1 to 3 respectively cover the lower limit, intermediate region, and upper limit region of the main process parameters in the claims. In Example 1, D1 is 2.6 μm and D2 is 0.8 μm; in Example 2, D1 is 3.4 μm and D2 is 1.6 μm; and in Example 3, D1 is 4.2 μm and D2 is 2.5 μm, all satisfying the requirements that D2 < D1 and D2 / D1 is 0.25-0.80. The Nd / Pr-rich grain boundary phase length coverage of the magnets obtained in Examples 1 to 3 is not less than 80%, Hcj is not less than 15 kOe, and (BH)max is not less than 35 MGOe, indicating that the present invention can achieve stable technical effects within the defined numerical range.

[0071] Example 2 represents the preferred conditions for the intermediate region, where the length coverage of the Nd / Pr-rich grain boundary phase reaches 91.6%, and the relative enrichment index of Ce in the grain boundary phase is 0.58, indicating that Ce mainly exists in Ce-containing R2Fe. 14In the B main phase, Nd / Pr is enriched in the grain boundary region and forms a continuous coating structure. The Hcj of Example 2 is 16.8 kOe, and (BH)max is 38.2 MGOe, indicating that it still has high coercivity and high magnetic energy product under high Ce utilization conditions.

[0072] Example 4 is a preferred solution under high Ce content conditions. Although the Ce content in the cerium-containing main phase alloy A is high, the grain boundary control alloy B provides a Nd / Pr-rich, low Ce grain boundary control component. Combined with a grain size gradient of D2 / D1 of 0.39, the length coverage of the Nd / Pr-rich grain boundary phase is increased to 93.2%, and Hcj reaches 17.3 kOe. This proves that the present invention still has good applicability to high Ce content magnets.

[0073] Comparative Example 1, using a single alloy method, failed to form a structure where the cerium-containing main phase alloy A and the grain boundary control alloy B worked in synergy. Although its Br and (BH)max were relatively high, the length coverage of the Nd / Pr-rich grain boundary phase was only 54.3%, and the relative enrichment index of Ce in the grain boundary phase was 1.12, indicating that Ce was significantly enriched in the grain boundary region, resulting in insufficient magnetic isolation effect of the grain boundary phase. Hcj was only 12.4 kOe, significantly lower than that of Example 2.

[0074] Although Comparative Example 2 employed a dual-alloy method, the grain boundary control alloy powder D2 was close to the cerium-containing main phase alloy powder D1, with a D2 / D1 ratio of 0.97, indicating no effective grain size gradient. The results showed that its Nd / Pr-rich grain boundary phase length coverage was only 66.8%, and Hcj was 13.6 kOe, demonstrating that the grain size gradient is crucial for the grain boundary control alloy B to be fully distributed among the main phase powder particles and to form a continuous grain boundary phase.

[0075] In Comparative Example 3, the excessively high Ce content in grain boundary control alloy B led to an increase in the average Ce content of the grain boundary phase to 6.2 at.%, a decrease in the average Nd+Pr content of the grain boundary phase to 30.4 at.%, a length coverage of only 71.5% for the Nd / Pr-rich grain boundary phase, and a decrease in Hcj to 13.1 kOe. This indicates that grain boundary control alloy B must maintain a compositional characteristic of being rich in Nd / Pr and low in Ce in order to effectively suppress Ce from entering the grain boundary phase and retain Nd / Pr in the grain boundary region.

[0076] In Comparative Example 4, the addition of grain boundary control alloy B was too low, only 1.5%, resulting in insufficient grain boundary control components. The length coverage of the Nd / Pr-rich grain boundary phase was only 63.2%, and the Hcj was only 12.9 kOe. This result indicates that the addition of grain boundary control alloy B needs to be controlled within the range of 3-12% to form a sufficiently continuous Nd / Pr-rich grain boundary phase.

[0077] Comparative Example 5 did not undergo secondary aging, resulting in insufficient redistribution of the grain boundary phase. The length coverage of the Nd / Pr rich grain boundary phase was 75.6%, and the Hcj was 14.0 kOe. This indicates that multi-stage aging, especially secondary aging, plays an important role in the continuity of the grain boundary phase and the improvement of coercivity.

[0078] In Comparative Example 6, the grain boundary control alloy powder had an excessively fine particle size, with a D2 / D1 ratio of 0.13, which is below the range specified in this invention. Although this sample achieved an Hcj of 15.1 kOe, its relative density decreased to 97.4%, Br decreased to 11.9 kG, and (BH)max was only 34.2 MGOe, lower than the 35 MGOe specified in the product claims of this invention, due to the increased oxidation tendency of the excessively fine powder and the local excess of liquid phase during sintering, which affected densification. This result indicates that a smaller D2 is not necessarily better; a D2 / D1 ratio controlled within the range of 0.25-0.80 is necessary to balance grain boundary control and high magnetic energy product.

[0079] In summary, this invention, through the synergistic design of "dual alloy composition division, powder particle size gradient, and grain boundary reconstruction during sintering aging," enables the coexistence of Ce-containing main phase grains and Nd / Pr-rich continuous grain boundary phases. The Nd / Pr-rich grain boundary phase has a length coverage of no less than 80% along the main phase grain boundary, and can achieve comprehensive magnetic properties of Hcj no less than 15 kOe and (BH)max no less than 35 MGOe under Ce-containing conditions. The above embodiments and comparative examples show that this invention has significant structural and performance advantages compared to the single alloy method, the dual alloy method without particle size gradient, the high Ce grain boundary control alloy method, the low grain boundary control alloy addition method, and the method that omits the second-stage aging process.

Claims

1. A method for preparing cerium-containing neodymium iron boron magnets, characterized in that, Includes the following steps: Step 1: Prepare cerium-containing main phase alloy A and grain boundary control alloy B respectively; in cerium-containing main phase alloy A, Ce enters R2Fe as one of the rare earth elements. 14 B is the main phase, and the content of Nd and / or Pr in the grain boundary controlled alloy B is higher than the content of Ce. Step 2: Vacuum melting and rapid solidification casting of cerium-containing main phase alloy A and grain boundary control alloy B are performed respectively to obtain cerium-containing main phase rapid solidification sheet and grain boundary control rapid solidification sheet. Step 3: The cerium-containing main phase rapid solidification sheet and the grain boundary regulating rapid solidification sheet are respectively subjected to hydrogen crushing and air jet milling to obtain cerium-containing main phase alloy powder with an average particle size of D1 and grain boundary regulating alloy powder with an average particle size of D2, and D2 < D1. Step 4: Under an inert atmosphere, mix the cerium-containing main phase alloy powder and the grain boundary control alloy powder, and add antioxidants and lubricants to obtain mixed magnetic powder; Step 5: The mixed magnetic powder is oriented and shaped in an orientation magnetic field, and then subjected to cold isostatic pressing to obtain an orientation compact; Step Six: The orientation compact is subjected to vacuum sintering and multi-stage aging treatment to form a continuous grain boundary phase rich in Nd / Pr during the sintering and aging process of the grain boundary control alloy B, and the continuous grain boundary phase rich in Nd / Pr encapsulates Ce-containing R2Fe. 14 By controlling the B main phase grains, Ce is suppressed from entering the grain boundary phase and Nd / Pr is retained in the grain boundary region, resulting in cerium-containing NdFeB magnets.

2. The method for preparing a cerium-containing neodymium iron boron magnet according to claim 1, characterized in that, The cerium-containing main phase alloy A comprises, by mass percentage: Nd 12.0-24.0%, Pr 3.0-8.0%, Ce 3.0-10.0%, B 0.90-1.08%, Co 0.2-2.0%, Al 0.10-0.80%, Cu 0.05-0.50%, Ga 0.03-0.40%, Zr 0.02-0.20%, with the balance being Fe and unavoidable impurities; wherein Ce accounts for 15-45% of the total molar amount of rare earth elements in the cerium-containing main phase alloy A.

3. The method for preparing a cerium-containing neodymium iron boron magnet according to claim 1, characterized in that, The grain boundary control alloy B comprises, by mass percentage: Nd 35.0-65.0%, Pr 10.0-30.0%, Ce 0-5.0%, Cu 5.0-20.0%, Ga 2.0-12.0%, Al 1.0-8.0%, Co 0-8.0%, with the balance being Fe and unavoidable impurities; the total mass percentage of Nd and Pr in the grain boundary control alloy B is not less than 50.0%, and the mass percentage of Ce is not more than 5.0%.

4. The method for preparing a cerium-containing neodymium iron boron magnet according to claim 1, characterized in that, In step two, the vacuum degree of vacuum melting is not higher than 5 Pa, and the melting temperature is 1350-1500℃; the rapid solidification casting is cooled by water-cooled copper rollers with a linear speed of 1.0-3.5 m / s, the thickness of the obtained cerium-containing main phase rapid solidification sheet is 0.15-0.45 mm, and the thickness of the obtained grain boundary controlled rapid solidification sheet is 0.10-0.35 mm.

5. The method for preparing a cerium-containing neodymium iron boron magnet according to claim 1, characterized in that, In step three, hydrogen crushing includes hydrogen absorption and dehydrogenation treatment; the hydrogen absorption pressure is 0.08-0.20 MPa, the hydrogen absorption temperature is 20-120℃, the dehydrogenation temperature is 450-600℃, and the dehydrogenation time is 2-6 h; the air jet milling is carried out under nitrogen or argon protection, the D1 of the cerium-containing main phase alloy powder is 2.6-4.2 μm, the D2 of the grain boundary regulating alloy powder is 0.8-2.5 μm, and the D2 / D1 ratio is 0.25-0.

80.

6. The method for preparing a cerium-containing neodymium iron boron magnet according to claim 1, characterized in that, In step four, the mass ratio of cerium-containing main phase alloy powder to grain boundary control alloy powder is 88-97:3-12; the amount of antioxidant added is 0.02-0.20% of the total mass of cerium-containing main phase alloy powder and grain boundary control alloy powder, and the amount of lubricant added is 0.02-0.15% of the total mass of cerium-containing main phase alloy powder and grain boundary control alloy powder; the oxygen content during the mixing process is controlled below 1000 ppm.

7. The method for preparing a cerium-containing neodymium iron boron magnet according to claim 1, characterized in that, In step five, the orientation magnetic field strength is 1.5-2.5T, the orientation forming pressure is 60-120MPa, the cold isostatic pressing pressure is 150-250MPa, the holding time is 30-180s, and the orientation direction of the obtained orientation compact is the easy magnetization direction of the cerium-containing neodymium iron boron magnet.

8. The method for preparing a cerium-containing neodymium iron boron magnet according to claim 1, characterized in that, In step six, the vacuum degree of vacuum sintering shall not exceed 5 × 10⁻⁶. - ²Pa, sintering temperature is 1030-1085℃, holding time is 2-6h; multi-stage aging treatment includes first-stage aging and second-stage aging, first-stage aging temperature is 850-930℃, holding time is 1-4h, second-stage aging temperature is 450-560℃, holding time is 2-6h.

9. The method for preparing a cerium-containing neodymium iron boron magnet according to claim 1, characterized in that, In step six, after multi-stage aging treatment, Ce-containing R2Fe is formed in the cerium-containing NdFeB magnet. 14 The main phase consists of a B phase, an Nd / Pr-rich grain boundary phase, and a low-melting-point grain boundary modified phase containing Cu, Ga, and Al. The Nd / Pr-rich grain boundary phase is continuously distributed along the grain boundaries of the main phase, and the length coverage of the Nd / Pr-rich grain boundary phase along the grain boundaries of the main phase is not less than 80%. The low-melting-point grain boundary modified phase containing Cu, Ga, and Al is located in the grain boundary triangle region and / or at the grain boundary.

10. A cerium-containing neodymium iron boron magnet, characterized in that, The cerium-containing NdFeB magnet is prepared by the preparation method according to any one of claims 1-9; the cerium-containing NdFeB magnet comprises, by mass percentage: 28.5-32.5% total rare earth elements, 0.88-1.08% B, 0.2-2.0% Co, 0.10-0.90% Al, 0.05-0.80% Cu, 0.05-0.60% Ga, 0.02-0.20% Zr, with the balance being Fe and unavoidable impurities; wherein Ce accounts for 15-45% of the total molar amount of rare earth elements, and the cerium-containing NdFeB magnet has a Ce-containing R2Fe. 14 The main phase consists of a B-type phase and a Nd / Pr-rich continuous grain boundary phase, wherein the Nd / Pr-rich continuous grain boundary phase encapsulates Ce-containing R2Fe. 14 The cerium-containing neodymium iron boron magnet has B main phase grains, and its intrinsic coercivity Hcj is not less than 15 kOe, and its maximum energy product (BH)max is not less than 35 MGOe.